Analysis of reported cases of arterial hypertension in the elderly population through the Hiperdia system, Itacoatiara-AM, between 2009-2011 (Research, Society and Development, 2024)
Objective: To evaluate the incidence of arterial hypertension and resulting deaths from diseases associated with hypertension in the elderly population in a non-metropolitan city in the state of Amazonas-Brazil. Methodology: This is an epidemiological study, based on secondary data, carried out by searching for scientific publications in databases such: SciELO, PubMed and Lilacs, in addition to that, data made Available by the WHO, IBGE and Brazil’s Ministry of Health has been used. Results: The incidence rates of arterial hypertension exhibit a greater participation of elderly females, in addition to the incidence and mortality rates being statistically superior than the state rates, in Itacoatiara-AM. Conclusion: This study evaluated the SAH scenario in a rural city on Amazonas, highlighting the need of actions oriented to prevent, guide and manage the clinical condition of arterial hypertension on the elderly population.